2013
DOI: 10.1002/cam4.70
|View full text |Cite
|
Sign up to set email alerts
|

Discordance in HER2 gene amplification in circulating and disseminated tumor cells in patients with operable breast cancer

Abstract: Human epidermal growth factor receptor 2 (HER2) gene amplification in circulating tumor cells (CTCs) and disseminated tumor cells (DTCs) might be useful for modifying Herceptin therapy in breast cancer. In the process of investigating the utility of a microfluidic platform for detecting HER2 gene amplification in these cells, we observed novel results on discordance of HER2 status. Peripheral blood (8.5 mL) and bone marrow (BM) (7.5–10 mL) were collected prospectively from patients with clinical stages I–IV br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Characterization of CTCs is important since it has been shown that therapeutic targets such as HER2neu may be found on CTCs, even when the primary tumor is HER2 negative. (37) Such findings would have clear significance for future clinical trials designed at targeted eradication of CTCs. The concept of “liquid biopsy”, including gene mutation analysis in cell-free DNA, holds promise of providing real-time snapshots of the microscopic tumor burden throughout treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Characterization of CTCs is important since it has been shown that therapeutic targets such as HER2neu may be found on CTCs, even when the primary tumor is HER2 negative. (37) Such findings would have clear significance for future clinical trials designed at targeted eradication of CTCs. The concept of “liquid biopsy”, including gene mutation analysis in cell-free DNA, holds promise of providing real-time snapshots of the microscopic tumor burden throughout treatment.…”
Section: Discussionmentioning
confidence: 91%
“…As any other tumor material (surgical specimen, biopsy, fine needle aspirate. ), CTC can be characterized with "omics" analyses: genomics, either focused on copy-number profiles (Kanwar et al, 2015;Neves et al, 2014;Polzer et al, 2014), ERBB2 amplification (Krishnamurthy et al, 2013;Mayer et al, 2011), point mutations (Deng et al, 2014;Fernandez et al, 2014;Markou et al, 2014;Pestrin et al, 2015;Schneck et al, 2013) or on DNA methylation (Chimonidou et al, 2013a(Chimonidou et al, , 2013b(Chimonidou et al, , 2011, transcriptomics (Mostert et al, 2015;Onstenk et al, 2015b;Powell et al, 2012;Sieuwerts et al, 2011) and proteomics. Among proteins of potential therapeutic interest, the estrogen and progesterone receptors (Nadal et al, 2012;Somlo et al, 2011), HER2 (Ligthart et al, 2013), Ki67 (Paoletti et al, 2015) and apoptosis and DNA-repair related proteins (Garcia-Villa et al, 2012;Smerage et al, 2013) have been investigated, together with PDL1 expression on CTC (Mazel et al, 2015) and many other potential biomarkers.…”
Section: Successes and Pitfalls Of Ctc Characterizationmentioning
confidence: 99%
“…1). Microfluidic platforms (CTC-chips) are based on devices with antibodycoated microstructures, which allow the mixing of blood cells through the generation of microvortices to significantly enhance the number of interactions between target CTCs and the antibody-coated chip surface (14)(15)(16). Such an approach enables the capture of large numbers of viable CTCs in a single step from whole blood without the need for an initial enrichment step.…”
Section: Isolation and Enrichment Of Ctcsmentioning
confidence: 99%